2005
DOI: 10.1084/jem.20051381
|View full text |Cite
|
Sign up to set email alerts
|

A nonclassical non-Vα14Jα18 CD1d-restricted (type II) NKT cell is sufficient for down-regulation of tumor immunosurveillance

Abstract: The importance of immunoregulatory T cells has become increasingly apparent. Both CD4+CD25+ T cells and CD1d-restricted NKT cells have been reported to down-regulate tumor immunity in mouse tumor models. However, the relative roles of both T cell populations have rarely been clearly distinguished in the same tumor models. In addition, CD1d-restricted NKT cells have been reported to play a critical role not only in the down-regulation of tumor immunity but also in the promotion of the immunity. However, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
252
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(275 citation statements)
references
References 28 publications
16
252
2
Order By: Relevance
“…With this background in which the predominance of the literature suggested that type I invariant NKT cells were protective against tumors based on a Th1 bias, it was surprising to find that NKT cells could also suppress tumor immunosurveillance based on their production of the Th2 cytokine IL-13 (93)(94)(95)(96)(97), even though they contributed to asthma or protected against some autoimmune diseases based on a Th2 bias. Recurrence of a murine regressor tumor was found not to occur if CD4 ϩ regulatory cells were depleted, and these CD4 ϩ cells were found to be CD1d-restricted NKT cells (93), not CD4 ϩ CD25 ϩ Treg cells (98). Similar findings were made for protection against lung tumors derived from the CT26 colon carcinoma, in which spontaneous immunosurveillance was not apparent without blocking this regulatory pathway (97,98).…”
Section: Regulatory Role Of Type I Nkt Cells In Autoimmunity Andsupporting
confidence: 66%
See 2 more Smart Citations
“…With this background in which the predominance of the literature suggested that type I invariant NKT cells were protective against tumors based on a Th1 bias, it was surprising to find that NKT cells could also suppress tumor immunosurveillance based on their production of the Th2 cytokine IL-13 (93)(94)(95)(96)(97), even though they contributed to asthma or protected against some autoimmune diseases based on a Th2 bias. Recurrence of a murine regressor tumor was found not to occur if CD4 ϩ regulatory cells were depleted, and these CD4 ϩ cells were found to be CD1d-restricted NKT cells (93), not CD4 ϩ CD25 ϩ Treg cells (98). Similar findings were made for protection against lung tumors derived from the CT26 colon carcinoma, in which spontaneous immunosurveillance was not apparent without blocking this regulatory pathway (97,98).…”
Section: Regulatory Role Of Type I Nkt Cells In Autoimmunity Andsupporting
confidence: 66%
“…Studies in other tumor models supported a role for NKT cells in the suppression of tumor immunity, for example in the protection by IL-12 and IL-18 against the liver metastases of a mouse renal cell carcinoma (101). These findings that NKT cells could suppress tumor immunity led to a paradox in the role of NKT cells in tumor immunity (98,102,103). Were the same cells mediating opposite effects based on their cytokine balance, or were there two different types of NKT cells that were mediating these opposing effects?…”
Section: Regulatory Role Of Type I Nkt Cells In Autoimmunity Andmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the major non-invariant human PBPC T cell population responding specifically to CD1d, as obtained following G-CSF mobilization in vivo, were highly Th1-like cells producing large amounts of IFN-γ and little if any IL-4. Like certain other significant aspects of the otherwise highly conserved NKT cell biology, this contrasts with the situation reported in the murine model, where non-invariant NKT were reported to suppress iNKT anti-tumor responses (30). 3 / 4 autograft recipients who were deceased due to relapse lacked detectable CD1d-reactive PBPC at transplant, the 4 th being the weakest responder, whereas 5 / 6 surviving patients had CD1d reactivity (p = 0.02).…”
Section: Discussioncontrasting
confidence: 59%
“…Type І NKT cells mediate both protective and regulatory immune functions, including anti-tumor responses, protection against pathogens, maintenance of transplant tolerance and inhibition of autoimmunity, whereas type ІІ NKT cells suppress antitumor surveillance in certain model systems [16,56] . A large mount of studies demonstrated the anti-tumor activity of NKT cells stimulated by α-GalCer or by IL-12 in vivo [57,58] .…”
Section: Nkt Cells In Tumor Immunitymentioning
confidence: 99%